Heparins: A Shift of Paradigm - Hemker, H. Coenraad; Al Dieri, Raed; Béguin, Suzette (Frontiers in Medicine, 2019)
Heparins inhibit the thrombin forming capacity of plasma, i. e., the endogenous thrombin potential (ETP), by their anti-thrombin (aIIa) activity, the anti-factor Xa (aXa) activity is of minimal importance. This holds for both unfractionated heparin (UFH) and low molecular weight heparin (LMWH) at aXa/aIIa ratios < 25. Clinical experience and epidemiological evidence show a direct relationship between the ETP and the risk of thrombosis and bleeding. Consequently, the therapeutic potency of a heparin is determined by its aIIa activity, i.e., the concentration of a domain in which 12 sugar flank the high affinity antithrombin-binding pentasaccharide (HA5) at one side. The response of individual plasmas to a fixed dose of any heparin is highly variable. This suggests that individualization of heparin dosage, on basis of the ETP, might reduce bleeding or re-thrombosis. There exist simple laboratory methods for both the ETP and the concentration of the active domain. These methods can be used both for unequivocally characterization of a heparin preparation and for controlling heparin therapy and allow arbitrary units relative to a standard to be abandoned. These tests are as robust as any hematological routine test but not yet routinely available, which severely encumbers progress in the field.